Prevalence of turnover intention among emergency nurses worldwide: a meta-analysis - Hui Ren; Yingchun Xue; Pan Li; Xin Yin; Wenhao Xin; Hongyan Li (BMC, 2024)
Abstract Aim To explore the prevalence of turnover intentions among emergency nurses across the globe, decision-makers should be offered evidence-based assistance. Background and introduction Compared with those of general nurses, the unique work environment and pressure significantly impact emergency nurses' turnover intention. High personnel turnover intention often hinders the provision of high-quality emergency services. Methods This study was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Published and unpublished papers were identified through electronic searches of PubMed, Web of Science, EMBASE, CINAHL, and the Cochrane Library from their establishment until February 1, 2023. The literature included in this study may encompass cross-sectional studies and longitudinal studies. Two researchers independently screened the literature, extracted data, and assessed the quality of the included studies while using the tool developed by Hoy and colleagues in 2012. Stata 17.0 was used for all the statistical analyses. Results This study included 12 articles by screening 744 articles, which included a total of 4400 nurses. All studies included in the analysis were cross-sectional. The overall prevalence of turnover intention among emergency nurses was 45%. Further analysis revealed that the turnover intention prevalence among emergency nurses in Asia was 54%, whereas in other regions, it was 38%. The turnover intention among younger nurses (61%) was significantly greater than that among older nurses (30%). Compared with the published scale, the self-developed scale resulted in a higher turnover intention rate of 52%, which was 41%. Conclusion The prevalence of emergency nurses' turnover intention is relatively high and shows an increasing trend, with noticeable variations across different regions and age groups. Notably, Asian nurses and those younger than 35.6 years exhibit a greater intention to turnover. Patient or public contribution There is no patient or public involvement, as this article is a meta-analysis. Implications for nursing and health policy Nursing managers, administrators, and policymakers must recognize the seriousness of high turnover intentions among emergency nurses and develop effective prevention strategies to address this issue globally.